2018
DOI: 10.1016/j.ejps.2017.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Gamma scintigraphic pulmonary deposition study of glycopyrronium/formoterol metered dose inhaler formulated using co-suspension delivery technology

Abstract: This gamma scintigraphy imaging study was the first to assess pulmonary and extrathoracic deposition and regional lung deposition patterns of a radiolabelled long-acting muscarinic antagonist/long-acting β-agonist fixed-dose combination glycopyrronium/formoterol fumarate dihydrate (GFF) 14.4/10μg (equivalent to glycopyrrolate/formoterol fumarate 18/9.6μg), delivered by pressurized metered dose inhaler (pMDI) using novel co-suspension delivery technology. In this Phase I, randomized, single-centre, single-blind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 27 publications
4
33
0
1
Order By: Relevance
“…The homogeneous bronchodilation observed in this study supports the findings from a gamma scintigraphy study in healthy subjects,24 which found that GFF MDI was deposited in all regions of the lungs. FRI is also able to provide an image-based, numeric measure of drug deposition in the lungs17 and, using patient-specific inhalation profiles, estimated that approximately 48% of the total delivered dose of glycopyrronium and formoterol fumarate from GFF MDI could be deposited in the lungs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The homogeneous bronchodilation observed in this study supports the findings from a gamma scintigraphy study in healthy subjects,24 which found that GFF MDI was deposited in all regions of the lungs. FRI is also able to provide an image-based, numeric measure of drug deposition in the lungs17 and, using patient-specific inhalation profiles, estimated that approximately 48% of the total delivered dose of glycopyrronium and formoterol fumarate from GFF MDI could be deposited in the lungs.…”
Section: Discussionsupporting
confidence: 90%
“…FRI is also able to provide an image-based, numeric measure of drug deposition in the lungs17 and, using patient-specific inhalation profiles, estimated that approximately 48% of the total delivered dose of glycopyrronium and formoterol fumarate from GFF MDI could be deposited in the lungs. These FRI-based deposition results were higher than the gamma scintigraphy study (a 2D-imaging technique using 99m Tc radiolabels) that reported a lung deposition of 38% of the emitted dose of GFF MDI 24. In this study of patients with COPD, the simulation provided information about total drug deposition characteristics of GFF MDI and aligned them with the regional airway volume and resistance characteristics observed.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“… 101 104 Taylor et al used γ-scintigraphy to assess the lung deposition of GFF MDI and placebo MDI (porous particles only) in ten healthy male volunteers. 105 Both GFF MDI and placebo MDI delivered a similar proportion of the emitted dose to the lungs (mean [SD] 38.4% [10.0] and 32.8% [10.2], respectively), with a very low amount of the dose subsequently exhaled (mean [SD] 0.25% [0.26] and 0.24% [0.13], respectively). 105 The proportion of GFF MDI and placebo MDI delivered to the lungs was similar to the result in healthy volunteers who received an ICS/LABA FDC delivered by MDI (mean [SD] 34.1 [9.3]).…”
Section: Highlighting the Clinical Benefits Of Dual Bronchodilation: mentioning
confidence: 99%
“…GFF MDI was first approved for the long-term maintenance treatment of airflow obstruction in patients with COPD in the USA in 2016 6 and is the first LAMA/LABA FDC available as an MDI. It has been shown to provide effective dose delivery to the whole lung in vivo, 7 as well as consistent aerosol performance in vitro, even in the presence of simulated patient-handling errors. 8 The pivotal Phase III PINNACLE-1 and PINNACLE-2 studies (NCT01854645 and NCT01854658) demonstrated the efficacy and safety of GFF MDI in patients with COPD from the USA, Australia, and New Zealand over 24 weeks.…”
Section: Introductionmentioning
confidence: 99%